Rhodolith beds and their onshore transport in Fuerteventura Island (Canary Archipelago, Spain) - Rebelo, Ana Cristina; Martín-González, Esther; Melo, Carlos S.; Johnson, Markes E.; González-Rodríguez, Alberto; Galindo, Inés; Quartau, Rui; Baptista, Lara; Ávila, Sérgio P.; Rasser, Michael W. (Frontiers in Marine Science, 2022)
Rhodoliths occur extensively around the shores of Fuerteventura Island in the Canary Archipelago, with Lithothamnion cf. corallioides being the most prominent species. A large number of rhodoliths end up washed onshore, the debris from which contributes to the formation of sediments constituting modern beaches. In a previous study by one of the co-authors (MEJ), the northern coast of Fuerteventura was shown to comprise various types of rhodolith deposits such as beach, platform overwash, tidal pools, coastal dunes, and others. An extraordinary example of stranded rhodoliths is located near Caleta del Bajo de Mejillones, approximately 3 km west of Corralejo, on the north coast of the island. The deposit forms a supratidal beach 120 m long and 10 m wide that sits above the landward termination of an extensive wave-cut platform eroded in basalt and exposed at low tide to a width of 130 m perpendicular to shore. Here, rhodoliths are very small (<3 cm) resembling popcorn, and the locality is known as the “Popcorn Beach”. Other examples are berms up to 150 m long and 9 m wide at Caleta del Bajo de Mejillones, or an exposed beach at Playa del Hierro with an area of more than 1500 m2 covered entirely of very coarse rhodolith sand. Extensive living rhodolith beds were found at a water depth of 22 m.